Quantitative Susceptibility Mapping-Derived Radiomic Features in Discriminating Multiple Sclerosis From Neuromyelitis Optica Spectrum Disorder - Yan, Zichun; Liu, Huan; Chen, Xiaoya; Zheng, Qiao; Zeng, Chun; Zheng, Yineng; Ding, Shuang; Peng, Yuling; Li, Yongmei (Frontiers in Neuroscience, 2021)
Objectives To implement a machine learning model using radiomic features extracted from quantitative susceptibility mapping (QSM) in discriminating multiple sclerosis (MS) from neuromyelitis optica spectrum disorder (NMOSD). Materials and Methods Forty-seven patients with MS (mean age= 40.00 ± 13.72 years) and 36 patients with NMOSD (mean age= 42.14 ± 12.34 years) underwent enhanced gradient-echo T2*-weighted angiography (ESWAN) sequence in 3.0-T MRI were included between April 2017 and October 2019. QSM images were reconstructed from ESWAN, and QSM-derived radiomic features were obtained from seven regions of interest (ROIs), including bilateral putamen, globus pallidus, head of the caudate nucleus, thalamus, substantia nigra, red nucleus, and dentate nucleus. A machine learning model (logistic regression) was applied to classify MS and NMOSD, which combined radiomic signatures, demographic information to assess the classification accuracy using the area under the receiver operating characteristic (ROC) curve (AUC). Results The radiomics-only models showed better discrimination performance in almost all deep gray matter (DGM) regions than the demographic information-only model, with the highest AUC in DN of 0.902 (95% CI: 0.840 - 0.955). Moreover, the hybrid model combining radiomic signatures and demographic information showed the highest discrimination performance which achieved the AUC of 0.927 (95% CI: 0.871 - 0.984) with 5-fold cross-validation. Conclusions The hybrid model based on QSM and powered with machine learning has the potential to discriminate MS from NMOSD.